PENGARUH LATIHAN DRIBBLE DENGAN METODE BERMAIN TERHADAP HASIL DRIBBLE SEPAK BOLA SSB MITRA UTAMA LAMPUNG SELATAN - Gunawan Gunawan; Imam Mahfud (Journal of Physical Education, 2022)
The purpose of this study was to determine whether there was an effect of dribble trainingwith the playing method on the dribble results of SSB Mitra Utama Lampung soccer. Thisstudy consisted of 15 samples aged 12 to 14 with a total sampling technique using the onegroup pretest posttest experimental method. The results of the study showed that there wasa significant effect of dribbling practice with the playing method on the results of right footand left foot dribbles.From the results of the t-test of right-footed and left-footed soccer dribbles and it can beseen that the right foot can see that t count is greater than t table (14,806 1,761) and asignificant p value of (0.000 0.05) this result ensures that there is a significant timedifference between Pretest and posttest dribble practice with the playing method on theresults of the SSB Mitra Utama South Lampung soccer dribble. From the data, the pretesttime lies on average 22.21 and when the posttest time averages 18.08 and it can be seenthat there is an increase based on the average difference, namely by 4.13From the results of the t-test for dribble soccer with the right and left feet and it can beseen that the left foot shows that t-count is greater than t-table (11.806 1.761) and asignificant p value of (0.000 0.05) this result ensures that there is a significant timedifference between pretest and posttest dribble practice with the playing method on theresults of the SSB Mitra Utama South Lampung soccer dribble. From the pretest time datalies an average of 22.82 and when the posttest time averages 18.86 and it can be seen thatthere is an increase based on the average difference of 3.95